The Behind Discourse on the Extension of the President's Term of Office - Putra, Azhari M. Hadi; Suryani, Nilma (Faculty of Law, Andalas University, 2023)
Abstract: since the beginning of the 2024 simultaneous General Election (Election) stage, even before that, there have been sideways issues regarding the implementation of the election, among which the most dominant is the issue or discourse about extending the term of office of the president and postponing the 2024 election. These two discourses have become polemic in the midst of Indonesian society because some of them support it and others clearly reject it for the main reason, namely the constitutional mandate must be the basis for organizing the state. the government as the ruler is then strengthened by an analysis of academic theory according to the study of scientist C. Wright Mills an American sociologist who wrote The Power Elite in 1956 in which he gave rise to an understanding of elite theory. An understanding of the election law can realize that the legal loophole for extending the term of office of the president has been closed so that this discourse is not appropriate to continue to be put forward because it violates the constitution, as well as delaying elections which are considered to violate the constitution. As for the decision of the Central Jakarta District Court (PN), it is considered that the decision is categorized as flawed in the constitutional law rules as explained by several legal experts. In conclusion, the emergence of discourses as mentioned above is nothing but an attempt by interested parties, in this case, the ruling elites who are in the current government circle to remain in their seats of office. To prevent this, it is mandatory for the community to understand and adhere to constitutional rules in carrying out the life of the nation and state. Keywords: Delaying the 2024 Election ; Legal Basis for Elections; Elite Theory; Central Jakarta District court Decision; Elite Interests